Hubungan Red Cell Distribution Width (RDW) dan Kadar Troponin I Pada Penyakit Kardiovaskuler di RS Islam Jakarta Cempaka Putih - Tri Ariguntar Wikanningtyas; Tri Wahyuni; Rahmini Shabariah; Arief Indra Sanjaya (Universitas Malahayati, 2024)
ABSTRACT Cardiovascular disease (CVD) remains a serious health issue, both in developed and developing countries. According to the World Heart Federation (WHF), global deaths due to CVD surged from 12.1 million in 1990 to 20.5 million in 2021. The World Health Organization (WHO) reported 17.9 million deaths from cardiovascular diseases in 2021. This study aims to investigate the relationship between Red Cell Distribution Width (RDW) and Troponin I levels in cardiovascular disease patients at Jakarta Islamic Hospital (RSIJ) Cempaka Putih from 2021 to 2022. An analytical cross-sectional design was employed from May to August 2023 at RSIJ Cempaka Putih. Variables studied included patient characteristics, hematological laboratory tests (White Blood Cell (WBC), Red Blood Cell (RBC), Platelet (PLT), Hemoglobin, Red Cell Distribution Width-Standard Deviation (RDW-SD), Red Cell Distribution Width-Coefficient of Variation (RDW-CV), and Troponin I), and EKG examinations. The study involved 70 inpatient CVD patients at RSIJ Cempaka Putih in 2021-2022 who met the inclusion and exclusion criteria. Data analysis was performed using Spearman’s Rho correlation test. The results showed no significant correlation between blood parameters (WBC, RBC, PLT, hemoglobin, RDW-SD, and RDW-CV) and troponin I levels. There was no significant correlation between blood parameters (WBC, RBC, PLT, hemoglobin, RDW-SD, and RDW-CV) with troponin I levels. Factors other than blood parameters measured in this study may play a more significant role in determining troponin I levels. Keywords: Red Cell Distribution Width (RDW), Troponin I, Cardiovascular, Hematology ABSTRAK Penyakit kardiovaskuler masih menjadi masalah kesehatan yang serius, baik di negara maju maupun berkembang. Kematian akibat penyakit kardiovaskular (CVD) melonjak secara global dari 12,1 juta pada tahun 1990 menjadi 20,5 juta pada tahun 2021, menurut World Heart Federation (WHF). Laporan WHO (2021) sebanyak 17,9 juta orang yang telah meninggal karena penyakit kardiovaskuler. Penelitian ini bertujuan untuk melihat hubungan Red Cell Distribution Width (RDW) dan kadar Troponin I pada penyakit kardiovaskuler di Rumah Sakit Islam Jakarta (RSIJ) Cempaka Putih tahun 2021-2022. Penelitian analitik dengan desain cross-sectional, dilakukan di RSIJ Cempaka Putih pada Mei-Agustus 2023. Variabel yang diteliti terkait karakteristik pasien penyakit kardiovaskuler (CVD), pemeriksaan laboratorium hematologi (White blood cell (WBC), Red blood cell (RBC), platelet (PLT), hemoglobin, Red Cell Distribution Width-Standard Deviation (RDW-SD), Red Cell Distribution Width-Coefficient of Variation (RDW-CV), dan Troponin I), serta pemeriksaan EKG. Penelitian melibatkan 70 pasien rawat inap CVD di RSIJ Cempaka Putih pada tahun 2021-2022 yang memenuhi kriteria inklusi dan ekslusi. Analisis data dengan uji korelasi Spearman’s Rho. Hasil menunjukkan tidak ada hubungan yang signifikan antara parameter darah (WBC, RBC, PLT, hemoglobin, RDW-SD, dan RDW-CV) dengan kadar troponin I. Tidak terdapat hubungan yang signifikan antara parameter darah (WBC, RBC, PLT, hemoglobin, RDW-SD, dan RDW-CV) dengan kadar troponin I. Faktor-faktor selain dari parameter darah yang diukur dalam penelitian ini mungkin lebih berperan dalam menentukan kadar troponin I. Kata Kunci: Red Cell Distribution Width (RDW), Troponin I, Kardiovaskuler, Hematologi